2017
DOI: 10.3892/ol.2017.6961
|View full text |Cite
|
Sign up to set email alerts
|

T‑cell immunoglobulin mucin‑3 as a potential inducer of the epithelial‑mesenchymal transition in hepatocellular carcinoma

Abstract: T-cell immunoglobulin mucin (TIM)-3 is an important member of the TIM gene family, which was thought to contribute to the progression of numerous types of cancer, including hepatocellular carcinoma (HCC); however, the mechanism underlying TIM-3 functions in HCC progression has not yet been extensively investigated. The present study aimed to investigate the function of TIM-3 in the metastasis of HCC and to determine whether the alteration of TIM-3 expression levels regulated the epithelial-mesenchymal transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…EMT is a biological process defined as a rigorously programmed shift from epithelial to mesenchymal cell features that plays a substantial role in embryogenesis and organ development and also tissue repair and regeneration, as well as tumor invasion and metastasis [27]. EMT is triggered and sustained by multiple molecular processes, which, in some cases, may be used as biomarkers.…”
Section: Emt and Hccmentioning
confidence: 99%
“…EMT is a biological process defined as a rigorously programmed shift from epithelial to mesenchymal cell features that plays a substantial role in embryogenesis and organ development and also tissue repair and regeneration, as well as tumor invasion and metastasis [27]. EMT is triggered and sustained by multiple molecular processes, which, in some cases, may be used as biomarkers.…”
Section: Emt and Hccmentioning
confidence: 99%
“…Lin et al reported a role of the T cell immunoglobulin and mucin-domain containing-3 (Tim-3) in regulating EMT occurrence and further metastasis of HCC in vitro [127]. As recently extensively reviewed by Liu et al, Tim-3 is a new discovered immune checkpoint molecule playing a relevant role in the development of HCC [128].…”
Section: Mucinsmentioning
confidence: 99%
“…A further mechanistic study [ 54 ] showed that tumor cell-intrinsic Tim-3 would promote HCC development by triggering auto-secretion of IL-6 and then accelerating tumor growth through the STAT3 signaling pathway. Moreover, overexpression of Tim-3 by introducing its lentiviral-expressing particles in SMMC-7721 cell line promoted cell migration and invasion by facilitating the epithelial-mesenchymal transition (EMT) [ 55 ]. These studies indicate that Tim-3 expression in HCC cells accelerates tumor growth through auto-secretion of IL-6 and enhanced metastatic ability of HCC cells by promoting EMT.…”
Section: Tim-3 In Time and Hcc Cellsmentioning
confidence: 99%